UMKM MENUJU ERA DIGITAL PADA KELOMPOK UMIK (USAHA MIKRO) DI DESA WORI KEC. WORI KAB. MINAHASA UTARA: MSMEs Towards the Digital Era in the UMIK Group (Micro Enterprises) In Wori Village, Wori District, North Minahasa Regency - Victorina Zusana Tirayoh; Lady Latjandu, Rita Taroreh , Rita Taroreh (Sam Ratulangi University, 2024)
In the current digital era, people have been encouraged to choose methods that are fast, easy, and efficient; therefore, MSME business actors must also act more quickly and efficiently in order to be able to keep up with current developments and trends that are occurring in society. These changing circumstances and progress require business actors to adapt and switch to using digital platforms. Therefore, digitalization can be the right solution to adapt to maintain business and even develop business in the future.The object of this service activity is in Wori Village, Wori District, North Minahasa Regency, which has an entrepreneurial group that is classified as a micro enterprise (umik). Microbusinesses are productive businesses owned by individuals and/or individual business entities where the total assets owned are a maximum of IDR 50 million.The aim of this activity is to develop and build MSMEs, in this case the microbusiness group (umik) in Wori village, to become a business group that is